2014
DOI: 10.1007/s00405-014-3387-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the correlation between nasal septal deviation and compensatory hypertrophy of the middle turbinate

Abstract: The aim of the study was to investigate the relationship between nasal septal deviation and the middle turbinate hypertrophy using computed tomography. In this retrospective analysis, we examined 77 patients with nasal septal deviation. The mucosal and bone structures of the middle turbinate and the angle of the septum were measured using radiological analysis. Measurements of the middle turbinate on the convex side were compared to those on the concave side. Measurements of the bony and mucosal structure area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…8 There was no evidence of ipsilateral middle turbinate hypertrophy in any of the three groups, rather the increasing angle of septal deviation was associated with increase in the incidence of contralateral middle turbinate hypertrophy, which is in consonance with the study results of Demir et al who found that the measurements of the bony and mucosal structure of the contralateral middle turbinate were greater and statistically significant. 9 The measurements of the bony and mucosal thickness of inferior turbinate by Orhanet al, revealed statistically significant difference between the ipsilateral and contralateral side in patients of deviated nasal septum, which is in consonance to our study results ( Figure 2). 10 Our study shows higher incidence of bulbous type concha on the contralateral side (11.3%) as compared to the ipsilateral side (8.6%) among the three groups, parallel to the study results of Stallman et al 4 Elahi et al, evaluated the association of septal deviation and chronic sinus disease and concluded that the increasing angle of septal deviation is associated with bilateral sinus disease, contralateral middle turbinate abnormalities and prominent ethmoidal bulla.…”
Section: Discussionsupporting
confidence: 93%
“…8 There was no evidence of ipsilateral middle turbinate hypertrophy in any of the three groups, rather the increasing angle of septal deviation was associated with increase in the incidence of contralateral middle turbinate hypertrophy, which is in consonance with the study results of Demir et al who found that the measurements of the bony and mucosal structure of the contralateral middle turbinate were greater and statistically significant. 9 The measurements of the bony and mucosal thickness of inferior turbinate by Orhanet al, revealed statistically significant difference between the ipsilateral and contralateral side in patients of deviated nasal septum, which is in consonance to our study results ( Figure 2). 10 Our study shows higher incidence of bulbous type concha on the contralateral side (11.3%) as compared to the ipsilateral side (8.6%) among the three groups, parallel to the study results of Stallman et al 4 Elahi et al, evaluated the association of septal deviation and chronic sinus disease and concluded that the increasing angle of septal deviation is associated with bilateral sinus disease, contralateral middle turbinate abnormalities and prominent ethmoidal bulla.…”
Section: Discussionsupporting
confidence: 93%
“…212 It may cause bilateral or unilateral congestion and is often associated with nasal valve collapse and compensatory turbinate hypertrophy. [212][213][214] The importance and effectiveness of septoplasty for NSD does not appear to be universally accepted. 215,216 Nasal valve collapse.…”
Section: Differential Diagnosis Of Rhinitismentioning
confidence: 99%
“…In other cases, these nasal infl ammatory processes result a dilatation of the venous sinuses or fi brosis with a non-effectivity of medical therapy [2]. In traumatic septal deviation, a common condition is inferior turbinate compensatory hypertrophy [3]. This condition is not only caused by mucosal enlargement, but also by bony hypertrophy of the inferior turbinate itself [4].…”
Section: Introductionmentioning
confidence: 99%